An annotated and illustrated checklist to Syzygium (Myrtaceae) I: Micronesia - Byng, James W.; Wei, Xiao; Lorence, David H. (Phytotaxa, 2019)
An annotated checklist of fourteen known Syzygium species from Micronesia with information on distribution, ecology and consulted specimens. Two new species are described, Syzygium guamense and Syzygium mesekerrak, one new synonym is made for species occurring in the region and S.nitidum is lectotypified. A key to all species and two plates with leaves, flowers and fruits of all native species are included to aid identification.